Providing a Revenue Model for Hosting Sport Events - Zahra Alipour Nadinluie; Abbas Nazarian; Logman Keshavarz (Shahid Bahonar University of Kerman, 2021)
The present study aimed to propose a revenue model for hosting the sports events in Iran. 220 university professors, sports experts, staffs of sports federations, and management agents of international sporting events participated in this study. A researcher-developed questionnaire was used for data collection. Factor analysis was conducted to verify the structure validity. SPSS 22 and PLS software were applied for data analysis. Based on the findings, 12 factors were found to be significant in the monetizing from hosting the sporting events. Sponsors, human resources, politics, governmental institutions, law, sport fields, scientific, security, government support, media, Facility development, and fans were the most important factors for revenue generation in hosting sports events. Managers, organizations, and the organizers of sporting events can use appropriate strategies in the fields of media, sponsors, security of the country, investment, fans, governmental institutions, development of sporting facilities and places, and policy by utilizing the results and model provided in the present study in order to generate money from sporting events.